2021
DOI: 10.21926/cr.2201003
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Cyclopalladated Polythiophene Imine Monolayer by Self-Assembly, Hybrid Doping and Electrochemical Polymerization: A Simple Way to Enhance Activity and Stability

Abstract: In this article, an approach to generate self-assembly cyclopalladated polythiophene imine monolayers (denoted as ITO@Pd-CPTIMs) is described. The monolayers were fabricated by combining self-assembly (SA), hybrid doping (HD), and electrochemical polymerization (ECP) called SA-HD-ECP. The catalytic activity and stability of the polymerized monolayers in the Suzuki coupling reaction were improved by modulating the structure and morphology in hybrid doping using different thiophene derivatives, concentrations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated that the catalytic activity of the mono-or bi-organometallic catalytic monolayers can be improved by quantifying film morphology, tuning the composition of different metals, elucidating the relative distributions of electrons (which are related to the electrical characteristics of the ligand), and modifying the support and synergy of hetero-bimetals [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Appropriate supports, such as silicon with a greater flat surface, can result in a high dispersion and reproducibility of ordered organometallic catalytic monolayers [21-23, 25, 36-38].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the catalytic activity of the mono-or bi-organometallic catalytic monolayers can be improved by quantifying film morphology, tuning the composition of different metals, elucidating the relative distributions of electrons (which are related to the electrical characteristics of the ligand), and modifying the support and synergy of hetero-bimetals [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Appropriate supports, such as silicon with a greater flat surface, can result in a high dispersion and reproducibility of ordered organometallic catalytic monolayers [21-23, 25, 36-38].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclopalladated ferrocenylimine and its selfassembly monolayer are the most efficient catalysts in Suzuki coupling reactions [25,26]. Catalytic monolayers with different ligands with Schiff-base groups and their complexes are used to catalyze coupling reactions [13,14,[27][28][29][30][31][32][33][34][35][36][37]. However, a few studies on chiral cyclopalladated brushes immobilized on supports in a coupling reaction in heterogeneous were reported [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%